Impact of a power plant cooling system on copepod and meroplankton survival (Bahía Blanca estuary, Argentina). - Hoffmeyer, Monica Susana (2005)
The impact of a power plant cooling system in the Bahía Blanca estuary (Argentina) on the survival of target zooplanktonic organisms (copepods and crustacean larvae) and on overall mesozooplankton abundance was evaluated over time. Mortality rates were calculated for juveniles and adults of four key species in the estuary: Acartia tonsa Dana, 1849 and Eurytemora americana Williams, 1906 (native and invading copepods), and larvae of the crab Chasmagnathus granulata Dana, 1851 and the invading cirriped Balanus glandula Darwin, 1854. Mean total mortality values were up to four times higher at the water discharge site than at intake, though for all four species, significant differences were only registered in post-capture mortality. The findin gs show no evidence of greater larval sensitivity. As expected, the sharpest decrease in overall mesozooplankton abundance was found in areas close to heated water discharge.